An Improved Feed-Forward Carrier Recovery Algorithm for Coherent Receivers With M -QAM Modulation Format - Zhou, Xiang (IEEE photonics technology letters, 2010)
An improved feed-forward carrier phase recovery method is proposed for coherent receivers using M-ary quadrature amplitude modulation-based modulation formats. It is shown that by introducing multiple cascaded feed-forward carrier recovery stages, the required compute power can be significantly reduced compared to the prior art using the single-stage-based blind phase search method.